2013
DOI: 10.5100/jje.49.s544
|View full text |Cite
|
Sign up to set email alerts
|

1G-32 Investigation of Operating Forces of the Automotive Tactile Switch regarding Various Positions

Abstract: The objective of this study is to investigate affective preference of the automotive tactile switch which influences package controllability and user satisfaction. In order to accomplish this objective, the independent variables for this experiment were package location (door trim, crash pad, steering wheel (L), steering wheel (R), center fascia, center console and overhead console) and operating force (1.5N, 2.0N, 2.5N, 3.0N and 5.0N). Furthermore, we constructed an automotive seating buck based on actual loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Displacement was set according to the specification of the switch used for switch A recording. The magnitude of the actuation force was selected based on the push switches used in general automotive products (Ban et al, 2013;Gaspar et al, 2017).…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Displacement was set according to the specification of the switch used for switch A recording. The magnitude of the actuation force was selected based on the push switches used in general automotive products (Ban et al, 2013;Gaspar et al, 2017).…”
Section: Stimulimentioning
confidence: 99%
“…However, as per reports, more elderly people prefer switches with lower actuation force than younger people (Shibano et al, 2002); thus, from the perspective of universal design, excessive actuation force is undesirable. Additionally, a survey on the correspondence between the actuation force of in-vehicle switches and their mounting positions reported that the preferred switch actuation force differs depending on the mounting position of the switches (Ban et al, 2013). This indicates that for certain switches, increasing the actuation force could reduce its usability.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulus received through sensory systems has a hierarchical structure that composes complex sensibility from a simple sensibility to make an overall feel of satisfaction or dissatisfaction (Choe, 2013). Therefore, in this study, overall satisfaction of operation at the top was set as dependent factor, and seven-point Likert scale was used for analysis.…”
Section: Dependent Factorsmentioning
confidence: 99%
“…Users preferred the operating force at around 2.5~3.0N, which also showed difference by the operation mode. In case of tapping zone where switch was comfortably pressed, an operating force of 2.5N was the most preferred, while in a reaching zone where switch was pressed by stretching hands and a grasping zone where hands were wrapped, an operating force at 3.0N was the most http://jesk.or.kr preferred (Ban et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…하지만 물리적 키보드 사용 시에 느껴지 는 촉각 피드백이 인간의 오감 중의 하나임에도 불구하고 감 성과의 관계를 다룬 연구는 활발하게 이루어지지 않았다. 실제로 스위치와 관련하여 감성과의 관계를 다룬 연구로 Ban et al(2013)는 사용자의 만족도에 영향을 끼치는 자동차의 스위치의 촉각과 관련된 감성 선호도를 연구하였다. 이 때, 만 족도에 영향을 미치는 스위치의 촉각을 탐색하는 데 있어 콘솔 과 같은 패키지의 위치와 조작력을 의미하는 힘의 2가지를 독 립변수로 고려하였다.…”
Section: Introductionunclassified